The Application Model of Political Ethics on the Government Bureaucracy during Covid-19 Pandemicin Ternate City - Situmorang, Jubair (International Journal of Criminology and Sociology, 2022)
This research has two objectives; Namely, first, it aims to examine more deeply the model of political ethics and actor bureaucracy and second to examine the application of ethical models of political actors and the Ternate bureaucracy. The research method used is qualitative. The data analysis technique uses content analysis by examining the data collected from semi-structured interviews and relevant documents and articles. The research results reveal that the Ternate City Government always appreciates the moral values that live in the Ternate community. Make it a guideline in issuing policies. As the center of government of Ternate City, Ternate is an inseparable part of the history of the Sultanate of Ternate, which still upholds cultural values in carrying out every social, religious, and political activity. This is symbolized by the noble values of the Ternate people, namely Kie se Gam nagogugumatitirara (six basic traditions that are firmly held) and Jou se NgofaNgare (what is in you is with me and what is in me is also in you). In various policies, especially during the Covid-19 pandemic, the City Government has put forward ethical values rooted in the Jou Se NgofaNgare philosophy, namely understanding what is in me and vice versa, what is inside of me. Also yours. The overall ethical values it contains are limited to the relationship between God and humans and manifest in political life and state administration. Furthermore, it was revealed that the Ternate City Government views that the relationship with the community is a complementary and necessary unit. Therefore, in its policy, the City Government of Ternate is very egalitarian and accommodating to people of different ethnicities and religions. This research shows that the Ternate City Government is required to obey the constitutional rules and accommodate and respect the cultural values that live in the community. The expected implication is that the constitutional constitution and cultural values in Ternate City, which contain ethical values, are applied by every political actor and a government bureaucracy to be fully aware of their people's duties and responsibilities.